Penggunaan Aksara Swara dan Aksara Rekan pada Papan Nama Jalan dan Papan Petunjuk Lokasi di Daerah Istimewa Yogyakarta (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2022)
On the nameplates of streets and location directions in Yogyakarta that apply Javanese script, Latin writing derived from foreign languages is transliterated using swara script and rekan script. This research will reveal the application of swara script and rekan script in the rules of writing Javanese script. This research is a qualitative descriptive. Data collection techniques use documentation and note-taking techniques. The analysis technique applied is to input a picture from each street sign according to the type of swara and rekan script used then writes an explanation of the relationship between the script and the Latin script below it. The findings of this study are that the swara script is used to write down vowel scripts that become syllables, especially those derived from foreign languages, to emphasize their pronunciation. The swara script cannot be used as a pair script so the carakan script contained in front of it must be turned off with pangkon. The rekan script is used to inscribe consonant scripts on foreign words that are still preserved originally. There are 2 ways to turn off consonant sounds, namely by using the pangkon symbol and using pairs from the carakan script in the next word. Keywords: Javanese Script; Nameplates of Streets; Yogyakarta.